Don't tell the Nazis : a novel - Skrypuch, Marsha Forchuk (Scholastic Press, 2019)
It is June 1941 and after the brutal rule of the Soviets the people of Krystia's small Ukrainian village are inclined to look on the German invaders as liberators; but soon the Nazis start rounding up Jewish Ukrainians, and Krystia is faced with a terrible choice--risk everything by helping her Jewish friends and neighbors to hide, or save herself and her family by doing nothing.